2023
DOI: 10.3389/fendo.2023.1114767
|View full text |Cite
|
Sign up to set email alerts
|

An insight into brown/beige adipose tissue whitening, a metabolic complication of obesity with the multifactorial origin

Abstract: Brown adipose tissue (BAT), a thermoregulatory organ known to promote energy expenditure, has been extensively studied as a potential avenue to combat obesity. Although BAT is the opposite of white adipose tissue (WAT) which is responsible for energy storage, BAT shares thermogenic capacity with beige adipose tissue that emerges from WAT depots. This is unsurprising as both BAT and beige adipose tissue display a huge difference from WAT in terms of their secretory profile and physiological role. In obesity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 213 publications
(268 reference statements)
1
32
0
Order By: Relevance
“…In contrast to short-term diet exposure, reduced UCP1 and PGC1α expression levels under 12 weeks of HFHFD exposure (Figure 2a) revealed that the dissipating capacity of BAT might have been impaired in profound obese or diabetic conditions. We predict that this may be pivoting from an adaptive state to an overburdened one, which aligns with several previous studies where mice were subjected to HFD for longer time periods [29,42]. Specifically, these studies demonstrated that the significant body weight gain over time due to high-fat diet challenge diminishes UCP1 and PCG1α expression in BAT [43].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to short-term diet exposure, reduced UCP1 and PGC1α expression levels under 12 weeks of HFHFD exposure (Figure 2a) revealed that the dissipating capacity of BAT might have been impaired in profound obese or diabetic conditions. We predict that this may be pivoting from an adaptive state to an overburdened one, which aligns with several previous studies where mice were subjected to HFD for longer time periods [29,42]. Specifically, these studies demonstrated that the significant body weight gain over time due to high-fat diet challenge diminishes UCP1 and PCG1α expression in BAT [43].…”
Section: Discussionsupporting
confidence: 89%
“…To elucidate the underpinning molecular mechanisms mediating the diet-induced BAT dysfunction across different time periods, we then investigated key biomarkers for thermogenesis and apoptosis. As whitened BAT is typically accompanied by diminished UCP1 and PGC1α thermogenic biomarkers [29], we first evaluated their expressions in the BAT. UCP1 and PGC1α were indeed altered in the BAT of mice fed an HFHFD (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAT can function as a “heat production factory”, with the UCP1 protein in mitochondria inner membrane mediating uncoupling thermogenesis when fueling lipids and glucose ( 34 ). However, the thermogenic potential of BAT can be significantly impaired with aging or the development of obesity, which is called the whitening of BAT ( 35 ). In elderly obese individuals, BAT in specific anatomical regions showed reduced content with less vascularization and lightened brown color.…”
Section: Diseases Correlated With the Functional Decline Of Batmentioning
confidence: 99%
“…Thus, if these results are recalculated on a whole-tissue (depot) basis, there may not be any lowering of UCP1 amounts at all (but such calculations are not generally made). The mice with whitened brown adipose tissue are also reported to present with lower metabolism (energy expenditure) [44,45], but this is generally expressed-physiologically erroneously-per body weight, a calculation process that automatically makes obese mice demonstrate low metabolic rate (as has been discussed elsewhere, e.g. [46][47][48][49]).…”
Section: Opposing Powers: Ucp1 Versus the Adipostatmentioning
confidence: 99%